Bed Bugs and Blood-Sucking Conenose - Philip G. Koehler; Jeff Hertz (EDIS)
This document is ENY-227, one of a series of the Entomology and Nematology Department, UF/IFAS Extension. Original publication date April 1993. Revised October 2005.